2016
DOI: 10.7554/elife.14592
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical organization of presubicular head-direction circuits

Abstract: Neurons coding for head-direction are crucial for spatial navigation. Here we explored the cellular basis of head-direction coding in the rat dorsal presubiculum (PreS). We found that layer2 is composed of two principal cell populations (calbindin-positive and calbindin-negative neurons) which targeted the contralateral PreS and retrosplenial cortex, respectively. Layer3 pyramidal neurons projected to the medial entorhinal cortex (MEC). By juxtacellularly recording PreS neurons in awake rats during passive-rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
119
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 88 publications
13
119
0
Order By: Relevance
“…Projections from presubiculum preferentially label axons in layer 3 and deep layer 1 of MEC and form thin septa in layer 2 MEC, while projections from parasubiculum terminate in relatively large clusters in MEC layer 2 (Witter et al, 1989; van Groen and Wyss, 1990). This is also supported at the single cell level by reconstructions of single axons from the presubiculum (Preston-Ferrer et al, 2016) and the parasubiculum (Burgalossi et al, 2011) to the superficial layers of the MEC. The connectivity from the presubiculum has been studied in detail by Witter and colleagues who showed that presubicular inputs target apical dendrites of layer 5 entorhinal neurons and also neurons in all other layers of entorhinal cortex (Caballero-Bleda and Witter, 1993; Wouterlood et al, 2004; Canto et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Projections from presubiculum preferentially label axons in layer 3 and deep layer 1 of MEC and form thin septa in layer 2 MEC, while projections from parasubiculum terminate in relatively large clusters in MEC layer 2 (Witter et al, 1989; van Groen and Wyss, 1990). This is also supported at the single cell level by reconstructions of single axons from the presubiculum (Preston-Ferrer et al, 2016) and the parasubiculum (Burgalossi et al, 2011) to the superficial layers of the MEC. The connectivity from the presubiculum has been studied in detail by Witter and colleagues who showed that presubicular inputs target apical dendrites of layer 5 entorhinal neurons and also neurons in all other layers of entorhinal cortex (Caballero-Bleda and Witter, 1993; Wouterlood et al, 2004; Canto et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
“…The presubiculum contains clusters, which are largely restricted to PrS L2, are surrounded by calbindin- positive cells ( Figure 8A ; Fujise et al, 1995; Preston-Ferrer et al, 2016). These clusters also stain for acetylcholinesterase ( Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presubicular projection may be essential for serially transferring the head direction signal from the ATN to the medial entorhinal grid cell system (Rowland et al, 2013; Preston-Ferrer et al, 2016). Other known projection targets of the PrS include feedback projections to the thalamus (van Groen and Wyss, 1990a,b; Ishizuka, 2001) and LMN (Allen and Hopkins, 1989; Gonzalo-Ruiz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of our tetrode recordings, we cannot deduce with certainty the layer specificity of our recorded head‐direction cells. However, results from a recent study (Preston‐Ferrer et al ., ) showing a decreased theta rhythmicity specific to layer 3 postsubicular neurons (compared to layer 2 neurons) are consistent with our own data. Layer 3 neurons were found to predominately project to the medial entorhinal cortex, whereas layer 2 neurons targeted the retrosplenial cortex, as well as contralateral presubiculum.…”
Section: Discussionmentioning
confidence: 99%